Consider the equation k x 2 − ( 2 k + 1 ) x y + k y 2 = 0 , where k , x , y ∈ Z + . Let G be the set containing all possible values of k . Find x ∈ G ∑ x − 1 .
Created in colaboration with Sam Zhou.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The given equation k y 2 − ( 2 k + 1 ) x y + k x 2 = 0 can be seen as a quadratic equation for y . Solving y in terms of x , we have y = 2 k 2 k + 1 + 4 k + 1 x . For y to be an integer, 4 k + 1 , which is odd, must be a square of an odd integer. :Let 4 k + 1 = ( 2 n + 1 ) 2 , where n is an non-negative integer. Then,
4 k + 1 ⟹ k = 4 n 2 + 4 n + 1 = n ( n + 1 )
Therefore,
k ∈ G ∑ k 1 = n = 1 ∑ ∞ n ( n + 1 ) 1 = n = 1 ∑ ∞ ( n 1 − n + 1 1 ) = 1 See note.
Note that for 4 k + 1 = ( 2 n + 1 ) 2 ⟹ k = n ( n + 1 ) for n ∈ N , Then
y ⟹ x y = 2 k 2 k + 1 + 2 n + 1 x = k k + n + 1 = n ( n + 1 ) n ( n + 1 ) + n + 1 = n n + 1
This means that there is a solution for every n ∈ N and therefore a k for every n , hence k ∈ G ∑ k 1 = n = 1 ∑ ∞ n ( n + 1 ) 1 is justified.
Solution by Sam Zhou:
k x 2 − ( 2 k + 1 ) x y + k y 2 = 0
Rearranging we get k = ( x − y ) 2 x y
1 + 4 k = 1 + 4 ⋅ ( x − y ) 2 x y = ( x − y ) 2 ( x − y ) 2 + 4 x y = ( x − y x + y ) 2 , so 1 + 4 k must be the square of an integer.
m 2 ≡ 1 ( m o d 4 ) for odd m ∈ Z + , so 1 + 4 k must be the square of an odd integer.
Let k n < k n + 1 . ∀ n ∈ Z + , ∃ k n s.t. 1 + 4 k n = ( 2 n + 1 ) 2 and there is always a pair ( x n , y n ) that satisfies x n − y n x n + y n = 2 n + 1 (i.e. x = n + 1 , y = n )
4 k n = ( 2 n + 1 ) − 1 = 4 n 2 + 4 n ⇒ k n = n 2 + n = n ( n + 1 ) ∀ n ∈ Z + . There exist an infinite number of values for k.
∴ x ∈ G ∑ x − 1 = i = 1 ∑ n k i 1 = i = 1 ∑ ∞ i ( i + 1 ) 1 = i = 1 ∑ ∞ ( i 1 − i + 1 1 ) = 1 since the series is a telescoping sum.
■
You don't need to enter text in LaTex. It is difficult, the sentences would not flow naturally, and it is not the standard in Brilliant.org. You should look at other problems. I have modified the problem format for you. The text editor also allows italic , bold and italic and bold .
From the given conditions of the problem, k must be of the form n(n+1), where n is a positive integer. Therefore k 1 = n 1 - n + 1 1 . This results in a telescopic sum whose value is 1.
Problem Loading...
Note Loading...
Set Loading...
Dividing by y 2 and solving the resulting quadratic we find y x = 2 k 2 k + 1 ± 4 k + 1 .
Since x , y are positive integers, this has to be rational, so 4 k + 1 is an odd perfect square, and k = a ( a + 1 ) for some positive integer a .
This condition is necessary, and it is also sufficient: any such k will give a positive rational result that can be expressed (by definition) as the ratio of two integers x , y .
So ∑ k ∈ G k 1 = ∑ a = 1 ∞ a ( a + 1 ) 1 = ∑ a = 1 ∞ ( a 1 − a + 1 1 ) = 1